Gravity Prediction from Anomaly Degree Variances - Fashir, Hassan Hashim; A. Kadir, Abd. Majid (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1998)
Most of the geodetic boundary value problems were solved in terms of integral formulae extended over the whole earth. These formulae presuppose the knowledge of some of physical quantities at every point on the physical earth surface. In reality these quantities are only measured at a relatively few points on land ,although there are sufficient measurements in large parts of the oceans. Hence prediction of physical quantities is essential to fill in the gaps. The prediction of missing points ~nd mean anomalies from anomaly degree covariances were investigated. The essential parameters of the covariance functions using anomaly degree variances were computed. The closed form of evaluating empirical covariance functions to compute gravity anomalies with their accompanying statistics were thoroughly discussed.